Physiological stress against simulated 200-m and 500-m sprints in world-class boat paddlers - Senakham, N.; Punthipayanon, S.; Senakham, T.; Sriyabhaya, P.; Sriramatr. S.; Kuo, C.-H. (Chinese Journal of Physiology, 2020)
To characterize physiological stress response against simulated short-distance sprints among world-class paddlers. Thirteen dragon boat gold medalists performed 200-m and 500-m simulated race trials on a kayak ergometer in a randomized, counter-balanced, crossover fashion. During the 200-m and 500-m sprints, oxygen consumption (VO2) increased from 8.7 to 31.2 ml/kg/min and from 8.0 to 32.7 ml/kg/min within 60 s, respectively. A plateau of 35 ml/kg/min below maximal VO2(VO2max) (39.7 ± 6.3 ml/kg/min) was reached at 75 s during the 500-m sprint. Respiratory exchange ratio dropped from 1.21 ± 0.16 to 1.07 ± 0.12 and 1.28 ± 0.13 to 1.06 ± 0.16 at 45 s, and resurged to 1.17 and 1.28 at the end of 200-m and 500-m sprints with lactate concentration reached 13 ± 2 and 15 ± 2 mM. Aerobic energy contribution to paddling power increases from ~10% for the first 15 s to ~80% for the last 15 s during the 500-m trial. Postexercise plasma thiobarbituric acid reactive substances increased by 376% and 543% above baseline after 200-m and 500-m trials (P < 0.001, between trials), respectively, followed by quick returns to baseline in 30 min (P < 0.001). Increased plasma creatine kinase (+48%) was observed only after the 500-m trial (P < 0.001, between trials), not 200-m trial. Our data suggest that muscle damage occurred only when maximal sprinting exceeding 2 min, highlighting an importance of volume than intensity on exercise-induced muscle damage.